Evaluation of urinary steroid profile in highly trained cyclists - Timon, R.; Olcina, G.; Maynar, M.; Munoz, D.; Caballero, M. J.; Maynar, J. I. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: A regular and intense physical exercise significantly modifies hormonal metabolism and there are many reports of a change in urine steroid levels accompanying the practice of sport. The aim of this study was to compare the urinary steroid profile between highly trained cyclists and untrained subjects. Methods: Urine levels of testosterone (T), epitestosterone (Epit), androstenedione, dehydroepiandrosterone (DHEA), androsterone (A), etiocholanolone (E), `-estradiol (E2), estrone (E1) and the most abundant urine metabolites of cortisol and cortisone, tetrahydrocortisone (THE) and tetrahydrocortisol (THF) were determined by gas chromatography-mass spectrometry in urine samples from a group of professional cyclists (n=15) submitted to maximum level training for several years and compared with urine samples from sedentary subjects (n=15). The relationships between T/Epit, A+E/ THE, A+E/ THF, DHEA/THE and DHEA/THF were also studied. Results: Cyclists showed lower urine levels of T, A, E and E2 and higher urine levels of androstenedione and E1 than sedentary individuals. A+E/THE and A+E/ THF ratios were higher in sedentary subjects than in cyclists. Conclusion: We conclude that cyclists showed a urinary steroid profile different from sedentary individuals, probably due to an adaptation to regular and intense physical training.